Optimised design of screw anchors in tension in sand for renewable energy applications. (1st December 2020) - Cerfontaine, Benjamin; Knappett, Jonathan; Brown, Michael John; Davidson, Craig; Sharif, Yaseen
Abstract: The offshore deployment of floating offshore structures such as wind turbines or wave energy converters is expected to strongly increase during the next decade, to face the appetite for green energy sources. The growing size of these structures' dimensions, inducing very large mooring forces, makes the anchoring solution adopted a critical issue for the commercial success of floating marine energy farms. The upscaling of the screw anchor technology from onshore to the offshore environment has been recently proposed as an efficient way of providing a large tension capacity while their installation generates far less noise and vibrations than impact pile driving. Most of recent studies on screw anchors have focused on separated geotechnical problems such as their uplift capacity or installation requirements. This paper incorporates within a single procedure geotechnical and structural constraints to calculate the optimal anchor geometry able to maximise the uplift capacity available. Performance envelopes for screw anchors have been derived in a parametric study, covering a broad range of soil conditions as well as in a case study, representative of offshore conditions. Results show that single screw anchors are more efficient (e.g. shorter and lighter) than driven piles to sustain tension loading. The results presented in this study support the applicability of screw anchors to be used as part of the mooring system for wave energy converters. However, tension requirements for tension-leg platform wind turbines would probably require the use of group of anchors. HIGHLIGHTS: Screw anchor design must encompass both geotechnical and structural constraints. Screw anchors can provide a large tensile capacity for offshore applications. Screw anchors are much more efficient than piles in tension.